Investigations into the effects of volatile biomass tar on the performance of Fe-based CLC oxygen carrier materials - Matthew E Boot-Handford; Nick Florin; Paul S Fennell (Environmental Research Letters, 2016)
In this study we present findings from investigations into interactions between biomass tar and two iron based oxygen carrier materials (OCMs) designed for chemical-looping applications: a 100% Fe _2 O _3 (100Fe) OCM and a 60 wt% Fe _2 O _3 /40 wt% Al _2 O _3 (60Fe40Al) OCM. A novel 6 kW _e two-stage, fixed-bed reactor was designed and constructed to simulate a chemical-looping combustion (CLC) process with ex situ gasification of biomass. Beech wood was pyrolysed in the first stage of the reactor at 773 K to produce a tar-containing fuel gas that was used to reduce the OCM loaded into the 2nd stage at 973 K. The presence of either OCM was found to significantly reduce the amount of biomass tars exiting the reactor by up to 71 wt% compared with analogous experiments in which the biomass tar compounds were exposed to an inert bed of sand. The tar cracking effect of the 60Fe40Al OCM was slightly greater than the 100Fe OCM although the reduction in the tar yield was roughly equivalent to the increase in carbon deposition observed for the 60Fe40Al OCM compared with the 100Fe OCM. In both cases, the tar cracking effect of the OCMs appeared to be independent of the oxidation state in which the OCM was exposed to the volatile biomass pyrolysis products (i.e. Fe _2 O _3 or Fe _3 O _4 ). Exposing the pyrolysis vapours to the OCMs in their oxidised (Fe _2 O _3 ) form favoured the production of CO _2 . The production of CO was favoured when the OCMs were in their reduced (Fe _3 O _4 ) form. Carbon deposition was removed in the subsequent oxidation phase with no obvious deleterious effects on the reactivity in subsequent CLC cycles with reduction by 3 mol% CO.